PERAN KUALITAS KELEKATAN IBU-ANAK, GENDER ANAK DAN RASIO GURU-ANAK TERHADAP KUALITAS HUBUNGAN GURU-ANAK USIA PRASEKOLAH - Hernawati, Neti; Lestari, Puji; Hildayani, Rini (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This research was to examine the role of mother-child attachment quality, child’s gender, and teacher-child ratio on teacher-child relationship quality of preschool children. This study involved 151 mother and teacher couple of preschool aged children that was choosed by incidental sampling. Data was collected through interview, self report with questionnaire, and observation. Data was analyzed by descriptive and logistic regression analysis. Results of the study showed that mother-child attachment quality and child’s gender had significantly influences toward teacher-child relationship quality. Meanwhile, teacher-child ratio had not significant influences toward teacher-child relationship quality. Based on the results of the study, it was important for parents to establish a secure attachment quality as a foundation for children to develop a close relationship with their teacher. Child’s gender also was paid attention by teacher to create teacher-child relationship quality in closeness dimension.